Pengaruh Struktur Modal dan CSR Terhadap Kinerja Keuangan Perusahaan Perbankan - Sitompul, Andreas Sebastian; Hendrik E. S. Samosir; Mei Hotma Mariati Munte (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to determine the effect of capital structure and corporate social responsibility on the financial performance of banking companies listed on the IDX for the period 2021-2023. The research method used is quantitative with panel data regression analysis. The research population consists of 47 banking companies, and the sampling method used is purposive sampling, resulting in a research sample of 34 banking companies with a total of 102 observations. The research results show that capital structure has a positive and significant effect on financial performance. Corporate social responsibility has a negative and significant impact on financial performance. This indicates that 99.9% of financial performance can be explained by capital structure and corporate social responsibility.